Using Electrocardiographic Findings Utilized International Standards in Athletes from Gorontalo Province - Nooradliah, Livia; Jusuf, Muhammad Isman; Pateda, Sri Manovita; Poetra, Jufri Febriyanto; Refiater, Ucok Hasian; Siregar, Muchtar Nora Ismail (Universitas Negeri Gorontalo, 2025)
Introduction: The rate of sudden cardiac death among athletes is notably high due to cardiovascular disorders. However, there is a significant gap in fundamental electrocardiographic (ECG) data within the athlete population, particularly in Gorontalo Province. This study aims to describe the electrocardiography findings using international standards for athletes in Gorontalo Province, aiming to prevent the risk of sudden death through proactive early detection via ECG.Methods: Utilizing a cross-sectional descriptive design, we employed total sampling techniques with a population of 80 active athletes. Data was collected through direct examinations using a high-quality, internationally standardized ECG device, followed by thorough descriptive analysis.Results: The results indicate that 90% of the athletes displayed normal ECGs, while 6.3% were classified as abnormal and 3.7% as borderline. Among the various athletic disciplines, endurance athletes showed a notable 9.4% rate of abnormalities, whereas athletes engaged in strength and mind sports consistently exhibited normal ECG results. Moreover, athletes in the productive age group (19–39 years) demonstrated a higher incidence of abnormalities than their counterparts in other age groups.Conclusion: This study emphasizes the importance of early electrocardiographic screening in athletes to identify potential cardiovascular risks and prevent sudden cardiac death. The findings reveal that most athletes in Gorontalo Province exhibit normal ECG results, followed by abnormal (6.3%) and borderline (3.7%) patterns, which undoubtedly require further investigation. These findings highlight the importance of regular ECG screening for active athletes to detect potential cardiovascular abnormalities early and prevent sudden cardiac events.Keywords: Athlete, cross-sectional studies, electrocardiography, international criteria, sudden cardiac death